2019
DOI: 10.1090/tran/7835
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic resurgence via integral closures

Abstract: Given an ideal in a polynomial ring, we show that the asymptotic resurgence studied by Guardo, Harbourne, and Van Tuyl can be computed using integral closures. As a consequence, the asymptotic resurgence of an ideal is the maximum of finitely many ratios involving Waldschmidt-like constants (which we call skew Waldschmidt constants) defined in terms of Rees valuations. We use this to prove that the asymptotic resurgence coincides with the resurgence if the ideal is normal (that is, all its powers are integrall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…This result improves the bounds found in Corollary 4.8 in [1]. We also point out that Lemma 1 is similar to results from the work in [28,29]. As a consequence, in Corollary 4 we show that the ideal of a Complement of a Steiner Configuration of points has expected resurgence, that is, its resurgence is strictly less than its big height (see in [30] for the first definition).…”
Section: Conjecture 3 (Stable Harbourne Conjecturesupporting
confidence: 86%
See 1 more Smart Citation
“…This result improves the bounds found in Corollary 4.8 in [1]. We also point out that Lemma 1 is similar to results from the work in [28,29]. As a consequence, in Corollary 4 we show that the ideal of a Complement of a Steiner Configuration of points has expected resurgence, that is, its resurgence is strictly less than its big height (see in [30] for the first definition).…”
Section: Conjecture 3 (Stable Harbourne Conjecturesupporting
confidence: 86%
“…It is clear from the definition that 1 ≤ ρ a (I) ≤ ρ(I). As pointed out in [27], DiPasquale, Francisco, Mermin and Schweig showed that ρ a (I) = sup{m/r : I (m) I r }, where I r is the integral closure of I r (see also [28] Corollary 4.14) .…”
Section: Conjecture 3 (Stable Harbourne Conjecturementioning
confidence: 92%
“…For squarefree monomial ideals I, [42, Corollary 3.6] or [9, Theorem 3.17] shows that the resurgence is bounded above by the maximal degree of a minimal generating set of the ideal I.…”
Section: Ideals With Expected Resurgencementioning
confidence: 99%
“…The resurgence of an ideal can be bounded by other invariants [4, Theorem 1.2.1], and it has been explicitly computed for certain ideals [1, 5, 11]. Related invariants have also been studied, such as the asymptotic resurgence [23], which can be computed via integral closures [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation